Monsignor T.J. Lynch celebrates 40th year (Raton Range Raton, New Mexico, 1978)
Newspaper article on Rev. Monsignor Thomas J. Lynch and the 40th anniversary celebration of his Ordination.
Master list item #: 24
File location is in the Raton File Cabinet
Keywords: Lynch, Thomas J; Sanchez, Robert F; Tafoya, Arthur; Lynch, William B; Marren, Mary; St. Patrick's Catholic Church; Raton Catholic Church; St. Mary of Lake Seminary; Our Lady of the Angels Seminary; Niagra University; Sacred Heart Church; Our Lady of Sorrows Church; St. Frances Xavier Church; Local History; Life and Customs; Churches; Celebration; Ordination; Pastor; Raton, New Mexico; Santa Fe, New Mexico; Chicago, Illinois; Albuquerque, New Mexico; Las Vegas, New Mexico; Clayton, New Mexico